Production of a sustainable primary airway cell model for respiratory research - O'Loughlin, Jonathan (2018)
The airway epithelium is one of the body’s front-line defences against environmental factors. It is known that in diseases such as asthma and COPD the epithelial layer is susceptible to damage which propagates inflammation and airway remodelling. Whilst primary airway epithelial cells have been key to furthering our knowledge of respiratory diseases, their practicality in research is limited by their short lifespan when cultured in vitro. Work completed by our research group previously highlighted the potential of BMI-1 in extending the lifespan, whilst maintaining plasticity, of bronchial epithelial cells for research purposes. The aim of this project was to build further on this work and determine whether HBECs engineered to express BMI-1 are comparable to normal human bronchial epithelial cells (NHBECs).